A rare case of fibrocystic disease in axillary accessory breast: a case report - Dar, Dawar Nadeem Aslam; Aslam, Maila (Journal of the Pakistan Medical Association, 2025)
Accessory breast is seen in 0.4 to 6% of women and its most common location is axilla. Normal breast diseases like fibrocystic disease, fibroadenoma, and carcinomas can also be seen in accessory breast. However, the true prevalence of fibrocystic changes in the accessory breast is not known. We present the case of a woman with right sided axillary swelling which was initially thought to be a lipoma but on histological examination, it was diagnosed as a case of accessory breast with fibrocystic changes. Thus, while dealing with patients having swelling in axilla, accessory breast with its diseases must be considered in differentials for timely diagnosis and management. When the mass is symptomatic, has poor cosmetic appearance, or there is uncertainty related to its diagnosis, excisional biopsy should be considered. Keywords: Fibrocystic changes, Accessory breast, Axilla.